Oral submucous fibrosis and its dermatological relation - Fareedi Mukram Ali; Ashok Patil; Kishor Patil; M C Prasant (Wolters Kluwer Medknow Publications, 2014)
Oral submucous fibrosis is a chronic insidious disease and is well-recognized as a premalignant condition. It is a collagen related disorder associated with betel quid chewing and characterized by progressive hyalinization of the submucosa. The oral submucous fibrosis needs to be differentiated from scleroderma showing oral manifestations, as these diseases have different pathogenesis and prognostic aspects. The patients of oral submucous fibrosis can approach the dermatologist. The aim of this article is to present concise overview of the disease and its dermatological relation.